The farming-inequality nexus, revisited: new insights from the gini project - Bogaard, Amy (2023)
In this talk we revisit the hypothesis that farming systems where production is limited by heritable material wealth (such as land) are associated with higher persistent levels of wealth inequality than systems where production is limited by (free) human labour. In previous work on western Eurasia, expansive ‘land-limited’ farming systems facilitated by animal traction were found to be associated with higher sustained levels of household inequality than smaller scale farming systems reliant on human labour (‘labour-limited’). New results from the ongoing GINI project (The Global Dynamics of INequalIty) expand the dataset on past household inequality in western Eurasia and in other world regions with very different agroecologies. We focus on case studies where archaeobotanical and/or preserved landscape features offer unusually clear insights into the nature of farming practice. These include remarkably intact agricultural landscapes in the southern Andes. In this cold and arid high-altitude setting, pre-Inkan societies developed a form of labour-limited agriculture. This regime changed abruptly with Inka colonization in the 15th century to a form of land-limited agriculture through forced labour. This agricultural trajectory continued under Spanish colonial rule, introducing use of animal traction along with new crops and domestic animals.